The Prominence of Psychosocial of Dysthymia Sufferers in Colleen Hoover's Novel Regretting You - Smarandreetha, Falsyawal; Ibrahim, Laila; Calista, Salsabila; Utungga, Rommel (Foremost Journal, 2024)
This article examines the psychosocial of dysthymia sufferers in Colleen Hoover’s Regretting You. The novel follows the story of a mother and daughter, Morgan and Clara, who lose their family members because of an accident that causes them to suffer dysthymia. This article investigates Morgan and Clara’s psychosocial of their dysthymia through their grieving over a family member’s death. Dysthymia is a type of chronic mood disorder characterized by long-term depressive symptoms that are less severe than those of major depression but persist for an extended period. Then, how is the psychosocial of dysthymia sufferers represented in Colleen Hoover’s Regretting You? The researchers took the data of this analysis by reading the novels thoroughly, approaching the analysis from Morgan and Clara's perspective, compiling a list of dialogues and narratives, and categorizing the collected data into specific themes. Using a qualitative method, the researchers in this analysis underline the comparison of psychosocial between Morgan and Clara illustrated in the novel. In conclusion, Morgan and Clara's experience of dysthymia during the loss of family members enriches their psychosocial changes in a mother-daughter relationship. The article highlights the prominence of psychosocial aspects through Morgan and Clara’s dysthymia based on the novel.